2016
DOI: 10.5588/ijtld.15.0672
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for <I>Mycobacterium tuberculosis</I> infection in 2–4 year olds in a rural HIV-prevalent setting

Abstract: SUMMARYBACKGROUND: Mycobacterium tuberculosis infection in children acts as a sentinel for infectious tuberculosis.OBJECTIVE: To assess risk factors associated with tuberculous infection in pre-school children.METHOD: We conducted a population-wide tuberculin skin test (TST) survey from January to December 2012 in Malawi. All children aged 2–4 years residing in a demographic surveillance area were eligible. Detailed demographic data, including adult human immunodeficiency virus (HIV) status, and clinical and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…In contrast, a study done by Khan and her colleagues in Malawi, showed that 1% childhood infection to TB bacilli, occurred either from an unknown casual contact in the community or a known household case [13]. Childhood infection to TB bacilli points out a recent transmission and serves as a sentinel for infectious TB, mostly adults in the community [15] [16].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study done by Khan and her colleagues in Malawi, showed that 1% childhood infection to TB bacilli, occurred either from an unknown casual contact in the community or a known household case [13]. Childhood infection to TB bacilli points out a recent transmission and serves as a sentinel for infectious TB, mostly adults in the community [15] [16].…”
Section: Discussionmentioning
confidence: 99%
“…The closeness of relation of contact to the Index case has been implicated in transmission of infection in some studies. 10,11,22,30 First degree relationships (spouse/son/daughter of the Index case) provide closer contact between IC and HC, increasing the chances of transmission of infection. First degree relations also tend to live together within the same household in closed spaces, resulting in higher chances of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Intimacy of contact, sleeping arrangements and sputum status of the TB patient have been implicated as risk factors in the transmission of TB, or even Acute Respiratory Infection to Household Contacts, especially underfive year old children who are generally confined to the house. 10,11,12 Limited social contact of very young children reduces their likelihood of becoming infected, unless the caregiver is the source case. However, additional caregivers like grandparents or extended family members taking care of the children during the day are also important.…”
mentioning
confidence: 99%
“…Children aged <2 years were excluded to minimise misclassification of infection status with false-positive TST due to recent bacille Calmette-Guerin (BCG) vaccination. 30 …”
Section: Methodsmentioning
confidence: 99%